Osteoporosis, Fear of Falling, and Restrictions in Daily Living. Evidence From a Nationally Representative Sample of Community-Dwelling Older Adults - Meyer, Felix; König, Hans-Helmut; Hajek, André (Frontiers in Endocrinology, 2019)
Background: There is a lack of studies examining the relationship between osteoporosis and fear of falling as well as the association of osteoporosis and restrictions in daily life due to fear of falling. Thus, the aim of this study was to investigate whether there is an association between the presence of osteoporosis and fear of falling as well as restrictions in daily life due to fear of falling. Methods: Cross-sectional data were used from a population-based sample of community-dwelling individuals in the second half of life (40 to 95 years; n = 7,808) in Germany. GP-diagnosed osteoporosis was used. Fear of falling as well as the restrictions in daily life due to fear of falling were collected in self-administered questionnaires. Multiple regression models controlling for sociodemographic, lifestyle and health-related variables were used to determine the association between osteoporosis and the outcome measures. Results: Logistic regressions showed that osteoporosis was associated with increased fear of falling in the total sample and in both sexes. In addition, regressions showed that osteoporosis was associated with restrictions in daily life due to fear of falling in the total sample and in women, but not in men. Conclusions: The present study showed that osteoporosis is associated with fear of falling and with restrictions in daily life due to fear of falling. Because effective interventions to treat the fear of falling are available, our study might help to address this target group more accurately.